Center-Pivot-Irrigated Soybean Cost-Return Budget - O'Brien, Daniel M.; Sartwelle III, James D. (My University, 1996)
This publication projects a budget that reflects expected income and costs based on center-pivot-irrigated soybean production in Kansas.
MF586_1996_10
Keywords: MF586; Economics; Crops; MF